The effect of social networks on forming a mental image of European countries "Britain, Sweden, Norway" according to a sample of Saudi youth - Asiri, Mohammed Ahmad (Arab Journal for Sciences and Research Publishing, 2022)
The study aimed to identify the impact of social networking on the formation of the mental image of some European countries. The study followed the descriptive survey method, and the questionnaire as a tool, it was distributed to a sample of (400) Saudi university students who follow the accounts of the European countries under study (Britain, Sweden, Norway), and the results showed: The nature of the mental image of the European countries in question formed among university youth of the Kingdom of Saudi Arabia after they were exposed to their pages on social networks came to a large degree and with an average of (4.26), and that most of the topics raised in the accounts of European countries on the networks Social media attracts university youth, “tourist topics” came first with a percentage of 35.5%, followed by “news” by 23.5%, then “social topics” by 12.8%, then “political topics” by 11%, then “history and culture” by 11%. 7%, then "cultural topics" by 6.8%. As for the nature of the information provided by these accounts to university youth, it came in the first place "informing the news and events in the country" by 33%, followed by identifying At the level of education and health” by 23.3%, then “acquaintance with the country’s culture” by 17%, then “recognition of the heritage and history of the country” by 12.5%, then “increase in general information about the country” by 6.8%. The researcher recommended conducting joint meetings between Saudi media professionals and those responsible for managing the accounts of the European countries in question, to achieve cooperation and exchange of experiences and communication and media skills. The researcher suggested conducting a study on the role of official accounts provided in Arabic for some European countries in raising awareness of their cultural and tourism issues.
Keywords: Social Networks; Mental Image Formation; Saudi Youth; European Countries